Análise comparativa de protótipos de sistemas de iluminação residencial fluorescente e LED alimentados por sistema fotovoltaico isolado - Barbosa, Danilo (2013)
This present work discusses two studies that were analyzed in parallel during its development. Two design of photovoltaic isolated systems was held applied as the power source for the residential lighting circuit only. The other study, includes a comparison between fluorescent lamps with LED lamps applying its in a residence, sizing through specific brazilian standards. In the case of LEDs, there are no standards for implementation the residential luminotechnical projects. For this reason, it was prepared primarily a luminotechnical project for fluorescent lamps, acconding to brazilian standards. Therefore, it was adopted as a criterion for the sizing parameter of the lamps´s luminous flux, being a common factor between the choose LED lamps and fluorescent lamps with looking over the specifications that resemble to fluorescent, especially about the lamps´s luminous flux, colour rendering índex (CRI), colour temperature, and also, with the best possible scattering of light on areas inside the residence. After the lamps being chosen, both the LEDs as the fluorescent it was made the load forecasting for both residential lighting circuit proposed, providing the basis for the photovoltaic dimensioning being independent of each other. The main objective it is evident the photovoltaic system, which applied to lighting circuit with LEDs or fluorescent lamps, bring better energy and financial benefits in their implementation in a residence. For study effects, it was chosen a house situated in Piraquara city, in Parana state, which in this time of the development of this work it was with some backlog in civil construction services. After being determinated the necessary parameters for photovoltaic systems dimensioning, as local solar radiation levels estimates annually and forecasting loads of lighting circuit among the study, it was developed a prototype representing a sampling test of the two photovoltaic projects, one for being applied to lighting of the residence consist of fluorescent lamps, and the other one applied to LED lamps. As sampling was chosen one of the rooms of the residence. Thus, the luminotechnical parameters were checked, like the measurements of illuminances verification of scattering of light in the room, procedures that were done according to brazilian standards. In Parallel, data were registered for the daily behavior of electrical parameters involved with the prototypes of photovoltaic systems, such as voltage and current input to the inverter, charge controller, among others. Finally, after evidencing the correct functioning of the prototypes developed, it was analyzed the data through charts as well as the analysis of the energy benefits and costs to implement the best photovoltaic system applied in isolated residential lighting.